NBA Ledang Foodstuff / Daniel Iskandar Arif Noor Akbar, Azamuddin Arsat, Mohd Azam Zahidin, Mohd Asyraf Mohd Aidil and Nik Ahmad Mawardhi Nik Zainal Rashid - Noor Akbar, Daniel Iskandar Arif; Arsat, Azamuddin; Zahidin, Mohd Azam; Mohd Aidil, Mohd Asyraf; Nik Zainal Rashid, Nik Ahmad Mawardhi (2018)
The objective of the case study is to investigate the problems faced by the Small medium Enterprise (SME) business in Malaysia, and recommend a solution to the problem based on analysis and theory. In this case study, we take NBA Ledang Foodstuff (NBA) as our guide to identify problem and solve the problem faced by the business.